2004
DOI: 10.2337/diacare.27.6.1412
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Acanthosis Nigricans and Insulin Sensitivity in Overweight Hispanic Children at Risk for Type 2 Diabetes

Abstract: OBJECTIVE -To investigate in a population of Hispanic children if 1) the presence of acanthosis nigricans (AN) is related to insulin sensitivity (S i ) independent of adiposity and 2) scale scoring AN severity adds to the clinical estimation of insulin sensitivity, above and beyond the presence or absence AN alone. RESEARCH DESIGN AND METHODS-The study population, 131 Hispanic overweight children (mean BMI percentile 97.0 Ϯ 3.1, 72 boys, 59 girls, ages 8 -13 years, mean Tanner stage 2.4 Ϯ 1.5) with a family hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 30 publications
10
62
3
2
Order By: Relevance
“…Although several studies have found AN to be an independent predictor of hyperinsulinemia others have not. [3][4][5][6][7] Very little information is available in this regard from rural areas of India. Therefore this study was carried out with the aim and objectives to study the association between acanthosis nigricans, and insulin resistance and to evaluate correlation of acanthosis severity, neck severity and neck texture severity with serum insulin especially in this rural part of central India.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have found AN to be an independent predictor of hyperinsulinemia others have not. [3][4][5][6][7] Very little information is available in this regard from rural areas of India. Therefore this study was carried out with the aim and objectives to study the association between acanthosis nigricans, and insulin resistance and to evaluate correlation of acanthosis severity, neck severity and neck texture severity with serum insulin especially in this rural part of central India.…”
Section: Introductionmentioning
confidence: 99%
“…AN is reportedly heavily influenced by genetic factors, being frequently found with Hispanic, Afro-American and Indian people, and infrequently encountered with Caucasians. This dermatological condition is associated with insulin resistance and metabolic disorders, and is known to be a good predictor of hyperinsulinemia, which can lead to DM-2 (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research have found that the presence of AN is an independent risk factor for T2DM since AN is associated with hyperinsulinemia and high BMI (Kong, et al, 2007;Kobaissi, Weigensberg, Ball et al, 2004). One third of our sample had high BMI.…”
Section: Presence Of Acanthosis Nigricans (An)mentioning
confidence: 57%
“…They found that AN was present in 17% of the children and adolescent in their sample. Another study of 131 obese children (BMI of 28.4+5.5) ages 7-13 found that up to 73% of the children had AN (Kobaissi, et al, 2004). Findings of overweight associated with AN in children and adolescents are significant.…”
Section: Presence Of Acanthosis Nigricans (An)mentioning
confidence: 96%
See 1 more Smart Citation